2005
DOI: 10.1007/s10194-005-0144-7
|View full text |Cite
|
Sign up to set email alerts
|

The patients’ perceptions of migraine and chronic daily headache: a qualitative study

Abstract: This study aimed to gain insight into the management of migraine and chronic daily headache (CDH) from the patients’ perspective. This article outlines the patients’ perceptions of migraine and chronic daily headache. Thirteen semi–structured interviews were carried out with patients suffering from IHS migraine. Five patients, due to their headache frequency of more than 15 headache days per month, were classed as CDH patients. The data were transcribed verbatim and analysed in accordance with the grounded the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 23 publications
5
42
1
Order By: Relevance
“…Quantitative studies have shown reduced quality of life in MOH [3-5], and other qualitative studies have described similar patterns of disability in relation to work, family and social life to those found in this study [27,36,37]. The participants were not passive in relation to this threat.…”
Section: Discussionsupporting
confidence: 79%
“…Quantitative studies have shown reduced quality of life in MOH [3-5], and other qualitative studies have described similar patterns of disability in relation to work, family and social life to those found in this study [27,36,37]. The participants were not passive in relation to this threat.…”
Section: Discussionsupporting
confidence: 79%
“…This differentiates our study from earlier ones that offered descriptions of the symptoms [17,20,22]. The meaning of being besieged arose because the body was temporarily dominated by the symptoms of the migraine attack, which made it impossible to function and fully participate in life and forced the women to put aside everything else to deal with their migraine.…”
Section: Discussionmentioning
confidence: 81%
“…
“ …I'm not very good at necessarily differentiating between the migraine and the bad tension headaches… I always think ‘oh, no I don't suffer from migraine’, but the doctor seemed to think that the way I was describing them that it was more migrainous. I guess I have never been a hundred percent certain of the differentiation between the two…”
The implication was that if the diagnosis is not well understood, the proper treatment will not be provided by the provider and/or will not be taken by the patient.…”
Section: Resultsmentioning
confidence: 99%